2016
DOI: 10.5688/ajpe807123
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of an Evidence-based Practice Pharmacology Course Using the Fresno Test

Abstract: Objective. To assess the effectiveness of an evidence-based practice (EBP) pharmacology elective course to teach EBP skills using the Fresno Test (FT). Methods. Pharmacy faculty members and medical librarians developed the elective course and offered it to two cohorts of doctor of pharmacy (PharmD) students. A pre/post intervention study design was used. Seven of 12 FT items were chosen to measure specific EBP skills: Ask, Access, Appraise and Apply. Pre/postcomposite and FT item mean scores were compared usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…10,23 Pharmacy school courses that effectively instruct EBP knowledge and skills have been described. 16,24,25 Despite agreement that EBM is a foundational knowledge and skill, the anecdotal practice of medicine still exists in busy clinical settings, putting pressure on the daily application of EBP. 7 To our knowledge, this is the first study to describe the instruction of EBP in the postgraduate pharmacy residency setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,23 Pharmacy school courses that effectively instruct EBP knowledge and skills have been described. 16,24,25 Despite agreement that EBM is a foundational knowledge and skill, the anecdotal practice of medicine still exists in busy clinical settings, putting pressure on the daily application of EBP. 7 To our knowledge, this is the first study to describe the instruction of EBP in the postgraduate pharmacy residency setting.…”
Section: Discussionmentioning
confidence: 99%
“…15 The test has been used in studies evaluating EBP in pharmacy students. 16 Composed of 12 items in open-ended, free-text questions, fill-in-the-blank questions and calculations related to two pediatric scenarios, the test is scored out of a total of 212 points. Taken in one 30-minute sitting, the test is scored using a standardized rubric with specific categories (not-evident, minimal and/ or limited, strong, excellent) including examples to improve rating on each item.…”
Section: Introductionmentioning
confidence: 99%
“…11 Further, the Fresno test has been used for pharmacy students but never validated. 20 However, conducting this research has revealed several drawbacks of the original instrument. To be considered "excellent," responses must be several statements long.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we used a sample of convenience rather than determining a target sample size to achieve statistically significant results. Based on our literature search conducted in March 2017, Gardner and colleagues 20 are the only researchers to publish on use of the Fresno to measure skill in EBM in pharmacy students. To assess their elective course, the authors used seven of the original 12 Fresno test questions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, medical students usually overrate their knowledge and skills about searching and evaluating the medical literature. Therefore, objective assessment of EBM is important …”
Section: Introductionmentioning
confidence: 99%